2005
DOI: 10.4049/jimmunol.175.2.1047
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocytes Express Abundant Surface Class I MHC and Efficiently Use Transporter Associated with Antigen Processing, Tapasin, and Low Molecular Weight Polypeptide Proteasome Subunit Components of Antigen Processing and Presentation Pathway

Abstract: Hepatic expression levels of class I MHC Ags are generally regarded as very low. Because the status of these Ags and their ability to present peptides are important for the understanding of pathogen clearance and tolerogenic properties of the liver, we set out to identify the factors contributing to the reported phenotype. Unexpectedly, we found that the surface densities of Kb and Db on C57BL/6 mouse hepatocytes are nearly as high as on splenocytes, as are the lysate concentrations of mRNA encoding H chain an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 43 publications
2
34
0
Order By: Relevance
“…Remarkably, induction of I-proteasomes in nonlymphoid organs, enabled purified hepatocytes to process CD8 ϩ T cell epitopes as efficiently as professional APC from lymphoid tissues. Consequently, our data support the concept that during infection hepatocytes become effective APCs (37). Two mechanisms for enhanced epitope generation could explain this effect: enhanced substrate turnover or altered cleavage site preference.…”
Section: Discussionsupporting
confidence: 86%
“…Remarkably, induction of I-proteasomes in nonlymphoid organs, enabled purified hepatocytes to process CD8 ϩ T cell epitopes as efficiently as professional APC from lymphoid tissues. Consequently, our data support the concept that during infection hepatocytes become effective APCs (37). Two mechanisms for enhanced epitope generation could explain this effect: enhanced substrate turnover or altered cleavage site preference.…”
Section: Discussionsupporting
confidence: 86%
“…Based on a large number of immunohistochemical studies in mice and humans, expression of MHC molecules on hepatocytes has been generally regarded as very low. 35,36 However, a recent report 11 has shown that these cells express abundant and conformationally stable MHC class I/peptide complexes with surface densities that are nearly as high as on splenocytes. Using quantitative flow cytometry techniques and calibration standards to adjust for the differences in cell size and autofluorescence between hepatocytes and splenocytes, it was demonstrated that, on a per cell basis, mouse hepatocytes express 7-to 16-fold higher levels of MHC class I molecules than splenocytes, whereas membrane densities were at least 30% to 75% as high as those estimated on splenic lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Using quantitative flow cytometry techniques and calibration standards to adjust for the differences in cell size and autofluorescence between hepatocytes and splenocytes, it was demonstrated that, on a per cell basis, mouse hepatocytes express 7-to 16-fold higher levels of MHC class I molecules than splenocytes, whereas membrane densities were at least 30% to 75% as high as those estimated on splenic lymphocytes. 11 Expression of both ICAM-1 and MHC class I is normally polarized. Consequently, it is likely that local densities of these molecules are higher at the basolateral surface of hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve days postvaccination in vivo antigen-specific cytolytic activity was evaluated cotransferring the following: 5 ϫ 10 6 5-(and 6-)carboxyfluorescein diacetate succinimidyl ester (CFSE) hi (2.5M; Molecular Probes) GFP [200][201][202][203][204][205][206][207][208] pulsed, 5 ϫ 10 6 CFSE int (250nM) hepatitis B virus envelope small subunit immunodominant epitope (HBs) [28][29][30][31][32][33][34][35][36][37][38][39] pulsed, and 5 ϫ 10 6 CFSE low (25nM) unpulsed per mouse. Eighteen hours later, single-cell suspension was prepared from lymph nodes draining the site of vaccination.…”
Section: In Vivo and In Vitro Cytotoxic T-lymphocyte Assaymentioning
confidence: 99%